2016
DOI: 10.1093/jpepsy/jsw059
|View full text |Cite
|
Sign up to set email alerts
|

Parents of Children With Food Allergy: Gender Differences in Perceived Impact and Perceived Food Allergy Severity

Abstract: Fathers who are less involved may be buffered from experiencing the impact of their child's health condition. Differences in involvement rather than other gender differences may explain discrepancies in mothers' and fathers' illness perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 43 publications
3
23
1
Order By: Relevance
“…Interestingly, we found partial support for our H4, suggesting that mothers are more likely to be more engaged in pressure-to-eat behaviours towards their food-allergic children than fathers. This finding is in line with studies of mothers and fathers of children with a food allergy or even other health conditions (e.g., [ 20 ]). It may indicate to the propensity for many fathers and mothers to engage differently in child-related health care.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, we found partial support for our H4, suggesting that mothers are more likely to be more engaged in pressure-to-eat behaviours towards their food-allergic children than fathers. This finding is in line with studies of mothers and fathers of children with a food allergy or even other health conditions (e.g., [ 20 ]). It may indicate to the propensity for many fathers and mothers to engage differently in child-related health care.…”
Section: Discussionsupporting
confidence: 92%
“…Food allergy refers to abnormal reactions to a food protein and is the most common source of critical allergic reactions that pose life-threatening complications [ 20 ]. Anaphylaxis is a common form of food allergy.…”
Section: Theoretical Foundations and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…95,96 Identification of sex differences in patients with perceived food allergy affect and severity indicated that female subjects reported increased effect of food allergy on health-related QoL related specifically to meal preparation, family social activities, stress/free time, and limitations on the affected child's social life. 97,98 However, investigators postulated that differences in the level of involvement in care might explain the different perceptions because fathers who more frequently attended medical appointments appreciated a greater effect on meal preparation than less-involved fathers. 97,98 Lower peanut threshold dose to elicit reaction, but not reaction severity, was identified as having a negative effect on food allergy-related QoL.…”
Section: Effects Of Food Allergymentioning
confidence: 99%
“…97,98 However, investigators postulated that differences in the level of involvement in care might explain the different perceptions because fathers who more frequently attended medical appointments appreciated a greater effect on meal preparation than less-involved fathers. 97,98 Lower peanut threshold dose to elicit reaction, but not reaction severity, was identified as having a negative effect on food allergy-related QoL. Parents of young children with food allergy reported significant mealtime behavioral concerns comparable with those in parents of children with type 1 diabetes and feeding disorders; these concerns correlated positively with parental perception of food allergy-related risk, parenting stress, and QoL.…”
Section: Effects Of Food Allergymentioning
confidence: 99%